Evaluación del sistema de tutorías académicas y su impacto en la formación integral de los estudiantes de la facultad de ciencias empresariales de la universidad técnica de Machala, periodo 2012-2013 y propuesta de un plan de políticas, normas y estrategias institucionales de regulación, ejecución y seguimiento. - Iñigüez Moreno, Jenny Isabel (2014)
This research work about "EVALUATION OF ACADEMIC TUTORING SYSTEM AND ITS IMPACT ON THE COMPREHENSIVE TRAINING OF STUDENTS OF BUSINESS STUDIES FACULTY OF THE TECHNICAL MACHALA UNIVERSITY, PERIOD 2012-2013 AND PROPOSAL OF A PLAN OF POLICIES, RULES AND STRATEGIES INSTITUTIONAL ADJUSTMENT, IMPLEMENTATION AND MONITORING " it makes a detailed analysis about academic tutoring in higher education and its contribution to the overall education of students, it is indispensable to establish a system of comprehensive tutorials structured properly, so academic tutoring that met its initial function that is aimed to support the training process, guiding the students since they begin the career to avoid failure and college dropout.